Clinical and cost-effectiveness of adapted cognitive behaviour therapy for non-cardiac chest pain: a multicentre, randomised controlled trial - Tyrer, Peter; Tyrer, Helen; Morriss, Richard; Crawford, Mike; Cooper, Sylvia; Yang, Min; Guo, Boliang; Mulder, Roger; Kemp, Samuel; Barrett, Barbara (BMJ Publishing Group, 2017)
Objective: To investigate the cost-effectiveness of a modified form of cognitive behaviour therapy for recurrent non-cardiac chest pain. Methods: We tested the effectiveness and cost-effectiveness of a modified form of cognitive behaviour therapy for chest pain (CBT-CP)(4-10 sessions) in patients who attended cardiology clinics or emergency medical services repeatedly. Patients were randomised using a remote web-based system to CBT-CP or to standard care in the clinic. Assessments were made at baseline and at six and 12 months. The primary outcome was the change in the Health Anxiety Inventory score at six months. Other clinical measures, social functioning, quality of life, and costs of services were also recorded. Results: 68 patients were randomised with low attrition rates at 6 and 12 months with 81% of all possible assessments completed at 6 and 12 months. Although there were no significant group differences between any of the outcome measures at either 6 or 12 months, patients receiving CBT-CP had between two and three times fewer hospital bed days, outpatient appointments, and A&E attendances than those allocated to standard care and total costs per patient were £1496.49 lower, though the differences in costs were not significant. There was a small non-significant gain in quality adjusted life years (QALY's) in those allocated to CBT-CP compared with standard care (0.76 vs 0.74). Conclusions: It is concluded that CBT-CP in the context of current hospital structures is not a viable treatment, but is worthy of further research as a potentially cost-effective treatment for non-cardiac chest pain.